Changes in Left Heart Geometry, Function, and Blood Serum Biomarkers in Patients with Obstructive Sleep Apnea after Treatment with Continuous Positive Airway Pressure - Kondratavičienė, Laima; Tamulėnaitė, Eglė; Vasylė, Eglė; Januškevičius, Andrius; Ereminienė, Eglė; Malakauskas, Kęstutis; Žemaitis, Marius; Miliauskas, Skaidrius (Medicina (Kaunas, Lithuania), 2022)
Background: Cardiovascular remodeling is essential in patients with obstructive sleep apnea (OSA), and continuous positive airway pressure (CPAP) therapy could improve these processes. Two-dimensional (2D) speckle-tracking (ST) echocardiography is a useful method for subclinical biventricular dysfunction diagnosis and thus might help as an earlier treatment for OSA patients. It is still not clear which blood serum biomarkers could be used to assess CPAP treatment efficacy. Objectives: To evaluate left heart geometry, function, deformation parameters, and blood serum biomarker (galectin-3, sST2, endothelin-1) levels in patients with OSA, as well as to assess changes after short-term CPAP treatment. Materials and Methods: Thirty-four patients diagnosed with moderate or severe OSA, as well as thirteen patients as a control group, were included in the study. All the subjects were obese (body mass index (BMI) > 30 kg/m2). Transthoracic 2D ST echocardiography was performed before and after 3 months of treatment with CPAP; for the control group, at baseline only. Peripheral blood samples for the testing of biomarkers were collected at the time of study enrolment before the initiation of CPAP therapy and after 3 months of CPAP treatment (blood samples were taken just for OSA group patients). Results: The left ventricle (LV) end-diastolic diameter and volume, as well as LV ejection fraction (EF), did not differ between groups, but an increased LV end-systolic volume and a reduced LV global longitudinal strain (GLS) were found in the OSA group patients (p = 0.015 and p = 0.035, respectively). Indexed by height, higher LV MMi in OSA patients (p = 0.007) and a higher prevalence of LV diastolic dysfunction (p = 0.023) were found in this group of patients. Although left atrium (LA) volume did not differ between groups, OSA group patients had significantly lower LA reservoir strain (p < 0.001). Conventional RV longitudinal and global function parameters (S′, fractional area change (FAC)) did not differ between groups; however, RV GLS was reduced in OSA patients (p = 0.026). OSA patients had a significantly higher right atrium (RA) diameter and mean pulmonary artery pressure (PAP) (p < 0.05). Galectin-3 and sST2 concentrations significantly decreased after 3 months of CPAP treatment. Conclusions: OSA is associated with the left heart remodeling process—increased LV myocardial mass index, LV diastolic dysfunction, reduced LV and RV longitudinal strain, and reduced LA reservoir function. A short-term, 3-months CPAP treatment improves LV global longitudinal strain and LA reservoir function and positively affects blood serum biomarkers. This new indexing system for LV myocardial mass by height helps to identify myocardial structural changes in obese patients with OSA.